CLEAT CHARACTERISTICS IN TERTIARY COAL OF THE MUARAENIM FORMATION, BANGKO AREA, SOUTH SUMATERA BASIN: Implications for Coalbed Gas Potential - Asep Kurnia Permana; Hermes Panggabean (Pusat Survei Geologi, 2011)
The sub-bituminous coal seams of the Muaraenim Formation commonly overlie claystone, sandstone or shaly siltstone. Coal seams are mostly dull to bright banded lithotype, well developed of cleat system, maceral composition dominated by vitrinite with rare inertinite and minor liptinite and mineral matter. In order to determine cleat systems and a possible relationship with the development of coalbed gas potential within the coal seams, detailed observation on coal seams characteristics, determination and measurement on cleat pattern and orientation, as well an insitu gas in place content measurement (Q1) within the coal measures were performed. Field measurement from outcrops demonstrate well-developed cleat within the coal seams, with high in spacing (âˆ‘ 8.93 cm) and moderate in density (0.1512/cm - 0.21/cm) and cleat aperture (1 - 3 mm). SEM analysis provides microcleat characteristics with a rare to medium density. Micro focus observation and examination on microcleat, face microcleats appears to be most prominent compared to butt microcleats. Microcleats also found mostly in open aperture. Gas content of the coal seam indicates a low to moderate methane content, with overall calculation of gas in place from six coal seams around 15.297,73 scf. Moderate level of mineral matter content in coal, as well as an excessive rare of clay minerals infill in microcleat may influence on increasing methane adsorption capacity. Moderate to high density and well continuity of cleat and microcleat could affect enhancing permeability, and plays important role in methane migration and production. Indeed, the coal characteristics and cleat systems of the Muaraenim Formation maybe favorable for coalbed gas potential.Keyword: Coalbed gas, Cleat systems, Muaraenim Formation